The concept of ‘touch’ in the formation of the Croatian and Turkish lexicon: The example of tactile verbs - Ida Raffaelli; Barbara Kerovec (LingBaW)
This paper explores the importance of the concept of ‘touch’ in the formation of the Croatian and Turkish lexicon. The main goals of the paper are 1) to investigate differences and similarities in conceptual mappings based on the concept of ‘touch’ in two typologically different and genetically unrelated languages by analyzing verbs referring to touch in Croatian and Turkish 2) to see to what extent the formation of tactile verbs differs with respect to lexicalization patterns in the two languages.